Investigating Problem-Based Learning Model's Impact on Student's Critical Thinking Skills in Environmental Conservation Context - Ahmad Irfan Ardiansyah; Alfyananda Kurnia Putra; Natalia Nikitina (JAMBURA GEO EDUCATION JOURNAL, 2024)
In the educational context of the 21st century, where critical thinking and problem-solving are essential skills, the Problem-Based Learning (PBL) model offers numerous advantages. In contrast to traditional learning models that only focus on knowledge transfer, PBL encourages students to solve real environmental problems, promotes active learning, and encourages the development of critical thinking skills to solve complex global issues. Environmental issues such as global warming, pollution, and other issues require students' ability to integrate various information and analyze, synthesize, and formulate holistic and comprehensive solutions. This research discusses the implementation of the Problem-Based Learning (PBL) model and aims to determine its effect on students' critical thinking skills in discussions related to the environment. The type of research applied was a quasi-experiment with a non-equivalent control-group design pre-test and post-test and the experimental class subjects were 29 and the control class was 32 students as a result of cluster random sampling. Data were collected in the form of essay tests and observations and then analyzed to determine significant differences using the t-test. The results of this study show that there is a significant difference in critical thinking skills with a value of p = 0.004 Î± 0.05 between the experimental class and the control class, where the experimental class gets a higher score of 71 compared to the control class of 61. In the event that learning involves interdisciplinary and abstract material such as environmental topics and aims to develop students' critical thinking skills, the PBL model can be a teacher's choice in implementing learning.